Risk Analysis of Potable Water Service Improvement in PDAM Malang City - Rona Rofida; Fadhila Fadhila; Calysta Deli Ad’hani (Talenta Publisher, 2026)
PDAM Malang has legally and technically provided potable drinking water through the Zona Air Minum Prima (ZAMP) program. Although most service areas have met ZAMP requirements, several areas still require improvements in service quality. The development of potable drinking water services requires substantial investment and faces technical, operational, and financial risks that may affect project performance and sustainability. This study analyzes the risks associated with improving potable drinking water services in PDAM Malang under a Public Private Partnership (PPP) scheme, focusing on risk allocation and mitigation strategies throughout the project lifecycle. A mixed-methods approach was employed, combining qualitative and quantitative techniques. Risks were identified through semi-structured interviews with five experts selected using purposive sampling. Risk assessment used the water sector risk matrix developed by PT Penjaminan Infrastruktur Indonesia, based on probability and impact scores ranging from 1 to 5. The results show that the dominant risks during the pre-construction stage were land acquisition delays and design errors, each with a risk score of 12. During construction, the highest risk was unclear output specifications, with a risk score of 20. In the operational stage, inaccurate life-cycle cost estimation and low initial service uptake were identified as the most critical risks, each scoring 25. The operational stage exhibited the highest overall risk level and was predominantly allocated to the private sector partner. These findings highlight the importance of appropriate risk allocation and effective mitigation strategies to ensure the sustainable delivery of potable drinking water services under a PPP framework.